Implementasi Program Edukasi dan Kepedulian Sosial dalam Mewujudkan Desa Berkualitas di Desa TambunImplementation of an Education and Social Awareness Program to Create a High Quality Village in Tambun Village: (Implementation of an Education and Social Awareness Program to Create a High Quality Village in Tambun Village) - Chalista Salsabilah Relanta; Dhea Adinda; A Putri Rahma Arisky; Tria Fajriana; Putri Nasywa Syakira; Jeni Rahayu Dara Danita; Zahwa Bilqis Zarakhan Ifo; Muhammad Dhani Al Farizhi; Aris Rismayadi; Pandu Nugroho; Gilang Satrio Wicaksono; Muhammad Irham Robbani; Ibnu Tafsier; Cahyadi Husadha (Jurnal Abdimas Ekonomi dan Bisnis, 2026)
The Community Service Program (Kuliah Kerja Nyata/KKN) is a form of student community engagement as an implementation of the Tri Dharma of Higher Education. The KKN program conducted by Group 76 of Universitas Bhayangkara Jakarta Raya was carried out in Tambun Village, Tambun Selatan District, Bekasi Regency, focusing on improving community education and social awareness. This study aims to analyze the implementation of community empowerment programs through education, health, and environmental activities in supporting the development of a quality village. This study used a qualitative approach with the Participatory Action Research (PAR) method, involving students and the community actively in the processes of problem identification, planning, implementation, and program evaluation. Data were collected through observation, interviews, and documentation during the KKN activities. The programs included BPJS Health Insurance education, parenting education, health programs through community exercise activities, and environmental programs through waste management by providing waste containers and conducting community clean-up activities with local neighborhood organizations. The results showed that the KKN programs had a positive impact on increasing community knowledge, awareness, and participation. Educational activities improved public understanding of health access and the importance of family roles in children’s development. Furthermore, health and environmental activities encouraged the community to adopt healthier lifestyles and improve environmental awareness. The PAR approach strengthened community involvement, allowing the programs to be implemented effectively and sustainably.